Impacts of the COVID-19 Pandemic on Wildlife in Huangshan Scenic Area, Anhui Province, China - Yuting Lu; Yaqiong Wan; Lanrong Wang; Dapeng Pang; Yinfan Cai; Yijun Wu; Mingxia Tang; Jiaqi Li; Baowei Zhang (Animals)
Human activities impact ecosystems globally, and understanding human–wildlife coexistence is crucial for species conservation. This study analyzed trends in local wildlife populations before and during the COVID-19 pandemic to assess their response to human disturbance. From 2017 to 2022, 60 camera sites were monitored, and seven species with the largest population size—excluding rodents—were selected for analysis. The results revealed that the presence of humans (p = 0.025) and domesticated animals (cats and dogs, p = 0.002) significantly decreased during the pandemic. Conversely, five species (except the Tibetan macaque and mainland serow) showed habitat expansion and population growth (p < 0.05), which may be related to their avoidance of human presence or artificial structures such as roads and tourism facilities. In addition, the analysis showed that most species, except the Tibetan macaque and wild boar, adjusted their activity patterns, showing increased diurnal activity when human disturbances were reduced (RR > 0). These findings suggest that species may adapt their behaviors to avoid human presence. This study highlights the negative impacts of human activities on local wildlife and emphasizes the need for stronger conservation and management efforts to mitigate human disturbances in scenic areas.